MIX BUFFERS AND COMMAND QUEUES FOR AUDIO BLOCKS (2013)
The subject disclosure is directed towards a technology that may be used in an audio processing environment. Nodes of an audio flow graph are associated with virtual mix buffers. As the flow graph is processed, commands and virtual mix buffer data are provided to audio fixed-function processing blocks. Each virtual mix buffer is mapped to a physical mix buffer, and the associated command is executed with respect to the physical mix buffer. One physical mix buffer mix buffer may be used as an input data buffer for the audio fixed-function processing block, and another physical mix buffer as an output data buffer, for example.